Dual Mycobacterial Invasion: A Case Report on Coexisting Tuberculosis and Nontuberculous Mycobacterium Infection - P. Prem Ananth; S. Raghul Raj; R. Anand; N. Nagarajan (Journal of Association of Pulmonologist of Tamil Nadu)
Tuberculosis (TB) and nontuberculous mycobacteria (NTM) infections are concerning for individuals with factors such as previous TB, diabetes, and chronic pulmonary conditions. Coinfections with TB and NTM, though rare, present diagnostic and therapeutic challenges. Mycobacterium kansasii, an NTM species, can cause pulmonary disease similar to TB, requiring thorough diagnostic approaches for effective treatment. This case report highlights a 61-year-old male farmer with a history of TB who was diagnosed with a TB-NTM (M. kansasii) coinfection after presenting with recurrent pulmonary symptoms.